Masyarakat Konsumen Sebagai Ciptaan Kapitalisme Global: Fenomena Budaya Dalam Realitas Sosial - Kushendrawati, Selu Margaretha (Makara Human Behavior Studies in Asia, 2006)
Global capitalism, which is born in the globalization process, has created consumption culture and consumer society— whose existence is seen just in the differences of their consumption commodities, and on and on consumes the signs and social status that marked on the commodities. In itself, global capitalism has the progressive-power which can help us in our daily live. However, the same progressiveness could bring the world in the unrecoverable and uncontrollable progressiveness. Progressive-power that inherent in the global capitalism has the tendency to lead the world into undetermined, injustice and hegemonic situation. This paper would discover this global capitalism phenomena, includes its positive result and negative effects on human’s live changes as the consumer society.